Leandro Losada, Maquiavelo en la Argentina. Usos y lecturas, 1830-1940, Buenos Aires, Katz Editores, 2019, 196 páginas - Bustamante Kuschel, Gonzalo (2020)
Fil: Bustamante Kuschel, Gonzalo. Universidad Adolfo Ibáñez; Chile.